Household Cost of Using Prosthetics and Orthotics Devices in Managing Physical Deformities for Patients Attending the Orthopedic Training Center, Nsawam - Moibi, A.S. (University Of Ghana, 2018)
Background: Mobility is one of the most important aspect of human existence but this is sometimes curtailed by diverse reasons including chronic conditions, malnutrition, war, aggressive behavior at home, the environment, and road traffic accidents. Assistive devices are significant in rehabilitation and support services, ensuring that people with disabilities and impairment have access and, mobility with little or no assistance.Costs of management of deformities with assistive devices service can be extremely high and sometimes unbearable for patients and their households. Objective: This study seeks to estimate the household cost of using prosthetics and orthotics devices in managing physical deformities for patients attending Orthopedic Training Center, Nsawam. Methodology: A descriptive cross-sectional cost-of-illness study design was used in the study. A structured questionnaire was used to collect data at the Orthopedic Training Center, for estimating Household Cost of Using Prosthetics and Orthotics Devices in Managing Physical Deformities. Data was obtained from two hundred and fourteen (214) patients. A systematic random sampling method was used to sample participants for the study. Direct costs was estimated from prosthetic and orthotics related and non-prosthetic and orthotics related services such as consultation, standard prosthetics and orthotics devices and repairs, food and transportation costs respectively. Indirect cost was estimated valuing the productivity losses to patients and household due to seeking care. Likert‘s Scale was used for the description of intangible cost of anxiety, pain and emotional trauma.Data would be sorted, cleaned and entered into STATA (version 14) for analysis and presentation of results. Results: The total cost of the management of physical deformities using Prosthetics and Orthotics devices was estimated to be GH₵ 123151.67 (USD 26258.35) with an average cost of GH₵ 575.4750935 (USD 122.7) per patient. The direct cost was estimated to be GH₵ 105574 (USD 22510.4) translating into 85.7% of the total cost while indirect was estimated to be GH₵ 17577.67 (USD 3747.9) translating into 14.27 % of the total cost. Cost of standard prosthetic and orthotics device was the highest price estimated to be GH₵ 69110 (USD 14735.60) of representing 56.1% of the total score. The intangible cost with the highest mean was the feeling of hopeless due to your disability (3.58) while the least dimension was the feel of aching discomfort when I am walking (2.3) Conclusion The cost incurred by household in managing physical deformities services is high. Policy and decision makers need to consider this in their strategic planning and budgeting for rolling interventions for persons with physical disability.
MPH.
Keywords: Household Cost; Prosthetics; Orthotics; Physical Deformities